Formes de l'idéal monarchique en Grèce - Pernot, Laurent (Orientalia, 2024)
Greek thinkers have developed numerous approaches to the model of an ideal monarch between the 4th and 1st century bce — in conformity with the historical evolution which saw the creation of great Hellenistic kingdoms during this period. Among the most important aspects, this paper examines, focusing on literary sources: 1) the historical roots of the monarchic concept, going back to archaic and classical times; 2) the philosophical image, which defines the virtues expected from the ruler, his duties and his beneficency; 3) the historical models, in particular that of Alexander, based on greatness and power; 4) the encounter between Greek values and Roman politics, when Greek authors, such as Polybius, were confronted with the figure of the consul and the imperator. According to the Greek point of view, monarchy appears as a form of government which lends itself to discussion and of which one must be wary. It must be controlled and justified in the name of ethical and religious norms that go beyond it.